The state of education: What awaits the next government? - Christine Farquharson; Andrew McKendrick; Nick Ridpath; Imran Tahir (Institute for Fiscal Studies (IFS), 2024)
In this report, we analyse the current state of the education system in England and set out the key challenges that the next government will inherit. This is not just a tale of despair. Compared with many other developed countries, England's education system does well in terms of student performance, and young people's skills have held up better through the COVID-19 pandemic than in many comparable countries. But there are substantial inequalities in attainment at every stage of education. Many of these inequalities have persisted for decades, but new issues have also emerged in recent years. Schools have seen a sharp increase in the number of pupils with special educational needs, a rise in absenteeism, and growing emotional and behavioural difficulties among young people. All the main political parties recognise these challenges and tackling these issues will be high on the agenda of the next Education Secretary.
Keywords: 330; Education and skills; Education; Further education; Schools; Inequality